Multiple Polypoid Lesions in the Colon: What Is Your Diagnosis? - Ünal, Hakan Ümit; Canpolat, Alper Tunga; Türk, Ali; Saruç, Murat (Turkish Journal of Gastroenterology, 2022)
Cite this article as: Ünal HÜ, Canpolat AT, Türk A, Saruç M. Multiple polypoid lesions in the colon: What is your diagnosis? Turk J Gastroenterol. 2022;33(8):720-721.